Cheating and Business Ethics - Baker, Wallace R. (Cambridge Scholars Publisher, 2019)
This volume is a unique collection of inspiring reflections designed to enhance the reader's understanding of both the importance and the relativity of business ethics. It invites experts and specialists of business ethics to explore threads from history, religion, philosophy and biology, but will also appeal to the thoughtful citizen, academic, businessman, banker and lawyer who has chosen to critically reflect upon the value of ethical conduct in today's world.The book draws from a rich mine of academic sources to consider how business ethics relate to today's key concerns, including wealth.